Prognostic value of PET/CT and MR-based baseline radiomics among patients with non-metastatic nasopharyngeal carcinoma - Kulanthaivelu, Roshini; Kohan, Andres; Hinzpeter, Ricarda; Liu, Zhihui Amy; Hope, Andrew; Huang, Shao Hui; Waldron, John; O’Sullivan, Brian; Ortega, Claudia; Metser, Ur; Veit-Haibach, Patrick (Frontiers in Oncology, 2022)
Purpose: Radiomics is an emerging imaging assessment technique, which has shown promise predicting survival among nasopharyngeal carcinoma (NPC) patients. Studies so far have focused on MR-based radiomic analysis. The aim of our study was to evaluate the prognostic value of clinical and radiomic parameters derived from both PET/CT and MR. Methods: Retrospective evaluation of 124 NPC patients with PET/CT and radiotherapy planning MR (RP-MR). Primary tumors were segmented using dedicated software (LIFEx .version 6.1) from PET, CT, contrast enhanced T1-weighted (T1-w), and T2-weighted (T2-w) MR sequences with 376 radiomic features extracted. Summary statistics described patient, disease and treatment characteristics. Kaplan Meier (KM) method estimated overall survival (OS) and progression free survival (PFS). Clinical factors selected based on univariable analysis and multivariable Cox model were subsequently constructed with radiomic features added. Results: The final models comparing clinical, clinical + RP-MR, clinical + PET/CT and clinical + RP-MR + PET/CT for OS and PFS demonstrated that combined radiomics signatures were significantly associated with improved survival prognostication (AUC 0.62 vs 0.81 vs 0.75 vs 0.86 at 21 months for PFS and 0.56 vs 0.85 vs 0.79 vs 0.96 at 24 months for OS). Clinical + RP-MR features initially outperform clinical + PET/CT for both OS and PFS (<18 months), and later in the clinical course for PFS (>42 months). Conclusion: Our study demonstrated that PET/CT-based radiomic features may improve survival prognostication among NPC patients when combined with baseline clinical and MR-based radiomic features.